Analysis of the Correlation Between Extracurricular Management and Students’ Academic Learning Motivation at SMA Muhammadiyah 1 Tangerang, Indonesia - Ruknan (Postgraduate, University of Mataram, 2025)
This study aims to analyze the correlation between extracurricular activity management and students’ academic learning motivation at SMA Muhammadiyah 1 Tangerang. The background of the research highlights the importance of effective extracurricular management as an integral part of character education and the holistic development of student learning motivation. The research employed a quantitative correlational method using a survey approach. The sample consisted of 100 randomly selected students from grades X and XI across various vocational programs. The instrument used was a structured questionnaire that had been tested for validity and reliability. Data analysis using Pearson’s correlation technique revealed a positive and significant relationship between effective extracurricular management and students’ academic motivation (r = 0.512, p < 0.05). The findings indicate that the better the management of extracurricular activities, the higher the students’ academic learning motivation. Therefore, schools are encouraged to continuously improve the planning, implementation, and evaluation of extracurricular programs as a strategic effort to enhance students’ academic performance holistically.